Bioactive Exopolysaccharide From Marine Bacteria Micrococcus sp.MRN-01. (2023) - Nisha, P; Paul, Elizabeth; Francis, Bismimol; Hyrunnisa, MA; Shahma, R.M; Johnson, Sona
Abstract: Many more undiscovered bioactive materials /compounds from marine bacteria, the list of the isolated marine strains to date, does not reflect the diversity of formspresent in the sea. Marine environment having higher sources of natural bio-compounds or polysacharide based biomaterials which are associated with solid surfaces as biofilms. Bacterial exopolysacharides is a biomaterials which showing a growing interest especially from biofilms and extreme marine environments. The main objective of this study is to characterize the bacterial exopolysacharide (EPS)and demonstrate the biological activity profile. Optimization of the exopolysacharide production from MRN-01, higher with the growth conditions of 96 hrs of incubation, 27 °C, 44.9 gm/L and optimize the total carbohydrate and total protein with various parameters, more production at 96 hrs, 27 °C, pH 9, ie, 128.23 gm/L, 100.26 gm/L respectively. EPS characterization by SEM, FT- IR analysis and revealed the presence of COOH, glucan, uronic acid, etc. EPS exhibit biological activities against pathogenic microbes and plant pathogenic fungi, express cyto toxicity against HELA cells and exhibiting antioxidant activity. Exo polysacharide production on steel surface influence corrosion with increased incubation.